KEADILAN KEWARISAN ISLAM TERHADAP BAGIAN WARIS 2:1 ANTARA LAKI-LAKI DENGAN PEREMPUAN PERSPEKTIF FILSAFAT HUKUM ISLAM - M. Lutfi Hakim (Al-Maslahah : Jurnal Ilmu Syariah, 2016)
Abstrack Justice is the core of law. However, the barometer of justice based on human’s consideration always changes according to time and place (tagayyur al-ahkām bi altagayyir al-azminah wa al-amkinah). The concept of legacy portion between man and woman, 2:1 in surah An-Nisā verse 11-12 always become a problem especiallywhen it is viewed from the equality of right and gender. Hence, the philosophy of Islamic law is then considered as an alternative to solve the problem. According to distributive justice perspective the legacy portion of 2:1 is fair since it iscommensurate with the responsibility and the right of both sides. It relates to the duty of a husband to take care of his parents after getting married. If then the woman take over the responsibility or do the same, it still do not change the portion. The problem above may be overcome through the concept of al-ahliyah al-wujūb in order to share the portion equally between man and woman.